Value-added tax cuts bring greatest relief to lower and middle income households - Stefan Bach; Niklas Isaak (DIW Economic Bulletin, 2017)
If the desire is to provide tax relief to households with lower and middle incomes in Germany, it is necessary to target the valueadded tax rather than the personal income tax. Lowering the standard value-added tax rate by one percentage point (from 19 to 18 percent) would mean relief worth 11 billion euro for consumers. The reduced value-added tax rate of seven percent should only be cut for food and local public transportation. Lowering it by two percentage points to five percent would generate relief equaling 3.8 billion euro. In total, these reform measures would generate fiscal relief of just under 15 billion euro. The simultaneous abolition of the remaining value-added tax would yield an overall revenue loss of 7.4 billion euro to the government. It could be abolished gradually in order to appropriately deal with adjustment issues or political resistance. Due to the regressive nature of the value-added tax, a major portion of the tax cuts would benefit lower and middle income groups, assuming companies pass on the relief to consumers by lower prices.
Keywords: H24; H22; D31; 330; value added tax; tax burden and income distribution; tax reform